Implementation of Covid-19 Health Standard at Elementary School in Yogyakarta - Widowati, Evi; Koesyanto, Herry; Wahyuningsih, Anik Setyo; Mayasari, R. Alma Dwi; Pitaloka, Fitri Rahmawati Dyah; Mambe, Sherly; Agustiani, Nurul Huda; As-Syifa, Al Fitra Salim; Permanahadi, Adriansyah (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
In the era of Covid-19 and the implementation of the new normal, schools have a difficult task because schools not only strive to continuously improve students’ academic abilities but must follow the basic principles of always keeping students, teachers and other staffs healthy and safe when they are at school. At the same time they must participate in helping the government in stopping the spread of the Covid-19. This study aims to describe the implementation of ventilation, duration and distance at schools; Educational Information Communication/EIC media; availability of Personal Protective Equipment/PPE; the availability of Covid-19 prevention facilities; and the level of knowledge of school staff and students regarding the prevention and handling of Covid-19 at schools. This study uses a qualitative descriptive research design. From the results of the study, it can be seen that school staff and students have a good level of knowledge regarding the management of prevention and handling of Covid-19 at schools and schools have implemented ventilation standards, duration, distance well too. However, the availability of EIC media, PPE and the availability of Covid-19 prevention facilities in schools are not in accordance with the expected standard.